Concise Synthesis and Biological Assessment of (+)‐Neopeltolide and a 16‐Member Stereoisomer Library of 8, 9‐Dehydroneopeltolide: Identification of Pharmacophoric Elements. Issue 25 (19th April 2013) - Fuwa, Haruhiko; Kawakami, Masato; Noto, Kenkichi; Muto, Takashi; Suga, Yuto; Konoki, Keiichi; Yotsu‐Yamashita, Mari; Sasaki, Makoto
Abstract We describe herein a concise synthesis of (+)‐neopeltolide, a marine macrolide natural product that elicits a highly potent antiproliferative activity against several human cancer cell lines. Our synthesis exploited the powerful bond‐forming ability and high functional group compatibility of olefin metathesis and esterification reactions to minimize manipulations of oxygen functionalities and to maximize synthetic convergency. Our findings include a chemoselective olefin cross‐metathesis reaction directed by H‐bonding, and a ring‐closing metathesis conducted under non‐high dilution conditions. Moreover, we developed a 16‐member stereoisomer library of 8, 9‐dehydroneopeltolide to systematically explore the stereostructure–activity relationships. Assessment of the antiproliferative activity of the stereoisomers against A549 human lung adenocarcinoma, MCF‐7 human breast adenocarcinoma, HT‐1080 human fibrosarcoma, and P388 murine leukemia cell lines has revealed marked differences in potency between the stereoisomers. This study provides comprehensive insights into the structure–activity relationship of this important antiproliferative agent, leading to the identification of the pharmacophoric structural elements and the development of truncated analogues with nanomolar potency.